Interactionist Dynamic Assessment in Academic Persuasive Writing: A Case of Two EFL Learners - Zahra kheradmand Saadi; Seyyed Ayatollah Razmjoo (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2017)
This study investigated the effects of interactionist dynamic assessment on improving academic persuasive writing of two Iranian EFL learners majoring in English Language and Literature. Qualitative analysis of the interactions between the mediator and learners and the drafts written by the learners indicated that using different types of mediation were effective in developing learners’ persuasive writing. In addition to the factors such as individual, time, and language feature which were shown to be integral in determining mediation, assessment of the two cases showed that factors such as mediator’s role, learners’ responsiveness to mediation, and agency were important in specifying mediation.